2023
DOI: 10.1111/jgs.18237
|View full text |Cite
|
Sign up to set email alerts
|

Frailty under COVID‐19 pandemic in Japan: Changes in prevalence of frailty from 2017 to 2021

Abstract: Background After the outbreak of the coronavirus disease 2019 (COVID‐19), “pandemic‐associated‐frailty” or profound health deterioration, in older adults has been considered a health concern. In this study, we sought to demonstrate whether pandemic‐associated‐frailty is occurring in Japan, where the population is aging, by showing the prevalence of frailty before and during the COVID‐19 outbreak, using the same method. Methods A total of 5222 older adults in Otawara City, Tochigi Prefecture, aged 70 and 75 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…These data are available for some populations, for example, frailty has been documented to have increased during the pandemic in Japan. 12 Changes in frailty indicators may affect calculations not only for elderly strata, but also younger ages. In some countries a large share of COVID-19 non-elderly deaths happened in young residents of LTCFs.…”
Section: Adjusting For Changes In Other High-risk Indicatorsmentioning
confidence: 99%
“…These data are available for some populations, for example, frailty has been documented to have increased during the pandemic in Japan. 12 Changes in frailty indicators may affect calculations not only for elderly strata, but also younger ages. In some countries a large share of COVID-19 non-elderly deaths happened in young residents of LTCFs.…”
Section: Adjusting For Changes In Other High-risk Indicatorsmentioning
confidence: 99%
“…The role of COVID‐19 in the development of frailty is currently not well understood 12 . Recently, preliminary studies have shown that the prevalence of frailty in the older adult population increased in the first and second years of the pandemic compared with the prepandemic situation 23 . For example, an Italian study of nursing home residents found a 19% greater decline in grip strength and a 22% greater decline in walking speed in COVID‐19 cases compared with controls between pre‐ and post‐COVID‐19 assessments, and multivariable logistic regression showed that COVID‐19 survivors had a fourfold increased risk of developing frailty compared with controls.…”
Section: Frailty After Covid‐19mentioning
confidence: 99%
“…[1][2][3][4][5] The transition from a usual lifestyle to one of prolonged self-restraint has been linked to an exacerbation of frailty among older adults, a condition referred to as "COVID-19 pandemic-associated frailty." 6 Frailty is characterized by a decline in physiological reserve capacity during old age, resulting in increased vulnerability to stress and a higher likelihood of transitioning to outcomes of functional impairment, states requiring long-term care, or death; however, it may be reversible through appropriate interventions that can restore a healthy state. 7,8 Indeed, reports during the COVID-19 pandemic have indicated that a subset of individuals exhibited improvement in frailty even amidst prolonged selfrestraint measures, despite initial predictions of worsening frailty.…”
Section: Introductionmentioning
confidence: 99%